Education and Occupational Health Assistance for Female Fishers in the Island Region of Bulang Lintang Island, Batam City - Ice Irawati; Chinta Yolanda Sari; Naily Nur Suliana; Sabrina Nurasdini (Sarana Ilmu Indonesia (salnesia), 2026)
Bulang Lintang Island, Batam City, is an archipelagic area where the majority of the population earns a living as traditional fishermen, including female fishers who carry a dual role as homemakers. However, this group continues to face challenges related to limited knowledge of occupational health and a high risk of health disorders resulting from repetitive and ergonomically inadequate work activities. This community service program aimed to improve female fishers' knowledge of occupational health through an educative and participatory approach. The implementation method employed was Participatory Action Research (PAR), consisting of four stages: preparation, socialization, education, and evaluation. The effectiveness of the educational intervention was assessed using a one-group pre-test and post-test design with Normalized Gain Score (N-gain) analysis. The program was conducted over two days, on May 12–13, 2026, on Bulang Lintang Island, involving 21 female fishers as participants. The results indicated an improvement in participants' knowledge, with an N-gain score of 0.34, which falls within the moderate category. In addition to the educational sessions, the program was supported by the distribution of leaflets and the provision of personal protective equipment in the form of foot protectors as a preventive measure against occupational hazards. This program was sufficiently effective in enhancing female fishers' knowledge of occupational health; nonetheless, sustained mentoring efforts remain necessary to achieve more optimal behavioral change.